Cool–Warm Temperature Stratification and Simulated Bird Digestion Optimize Removal of Dormancy in Rosa rugosa Seeds - Gao, Peng; Dong, Jie; Wang, Sihan; Zhang, Wuhua; Yang, Tao; Zhang, Jinzhu; Che, Daidi (Frontiers in Plant Science, 2022)
Rosa rugosa Thunb. has been explored multi-function in medicinal, edible, cosmetic, ornamental and ecological etc. However, R. rugosa natural populations have recently declined substantially in China, besides of global climate change, this species also has the defect of limiting the reproduction of itself such as the hard-to-release seed dormancy. In this study, only 30% of R. rugosa seeds were viable, and the others were incompletely developed or diseased seeds. Without stratification, morphologically complete viable seeds imbibed water but those seeds could not germinate even after seed husk removal under suitable condition to exhibit a physiological dormancy. After cold (4 °C) and warm (18 ± 2 °C) stratification, macromolecular substances containing carbon or nitrogen accumulated, and respiration, antioxidant enzyme activity, and gibberellin (GA3) /abscisic acid (ABA) and auxin (IAA)/ABA ratios increased significantly in seeds. Water absorption also increased as endocarps softened. Thus, physiological dormancy of seed was broken. Although warm and cold stratification increased separation between endocarp and embryo, the endocarp binding force was removed insufficiently, because only 10.20% of seeds germinated. Therefore, stratified seeds were treated with simulated bird digestion. Then, folds and cracks in loosened endocarps increased permeability, and water absorption rate increased to 64.43% compare to 21.14% in cold and warm stratification treatment. With simulated digestion, 24.20% of radicles broke through the endocarp with plumules and cambiums to develop into seedlings. Thus, the seed dormancy type of R. rugosa is physiological as seeds imbibed water and possessed fully developed embryos with a low growth potential in combination with a mechanical constraint from the endocarp. Cold stratification helped remove physiological dormancy, and additional warm stratification accelerated the process. The optimal stratification treatment was 4 °C for 45 d followed by 18 ± 2 °C for 15 d. After warm and cold stratification, simulated bird digestion broke the mechanical constraint from the seed covering layers. Based on this research, production of R. rugosa seedlings can be greatly increased to help protect the species from further declines.